HALAL-LABELED FOOD SHOPPING BEHAVIOR: THE ROLE OF IMAGE, TRUST, AND SATISFACTION WITH ATTITUDE - Muhammad Ridwan; Luki Adiati Pratomo (Jurnal Ekonomi Trisakti, 2023)
This research aims to examine the shopping behavior of halal-labeled food and the role of several factors in shaping consumer attitudes. Indonesia is a country with the largest Muslim population in the world, leading to high consumption of halal products. The demand for halal food continues to rise in the global market, with the halal food industry expected to reach trillions of dollars by 2027. Brand image, trust, and satisfaction are believed to influence consumer attitudes in purchasing halal-labeled food. This study employs a quantitative approach with a survey method and a questionnaire as the data collection instrument. Respondents are asked to assess variables related to shopping behavior of halal-labeled food using a Likert scale. The research findings conclude that brand image, trust, and satisfaction positively influence consumer attitudes in buying halal-labeled food. Therefore, companies need to enhance brand image, strengthen trust, and ensure customer satisfaction to improve consumer attitudes towards halal-labeled food. By optimizing these factors, consumers are expected to be more inclined to purchase and consume halal food products, thereby supporting the growth of the halal food industry in Indonesia. The managerial implications of this research suggest that companies should reinforce their brand image, enhance consumer trust, and ensure customer satisfaction to cultivate positive attitudes towards halal-labeled food products